The Category of Suppositive Tense in French (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article is about the category of suppositive tense in french. We know that phraseological units (hereinafter FB) are distinguished from other linguistic units by their communicative nature. According to A.G.Nazaryan, French FBs are divided into non-communicating and communicative types, and according to the words of M. Peckman, all FBs of the language are divided into word equivalent and sentence equivalent. units (word units and sentence units) can be separated.